Behavioral Determinants of Investor Decisions in ESG Investment Flows: Emerging Trends and New Developments - Hamal, Janga Bahadur; Sharma, Dilli Raj; Niroula, Arjun Kumar; Poudel, Janak Kumar; Pant, Ganesh Datt (Nepal Journal of Multidisciplinary Research, 2025)
Background: Environmental, social, and governance (ESG) investing has emerged as a pivotal mechanism for channeling global capital toward sustainability-oriented assets, reshaping contemporary financial markets and investor behavior. Hence, the paper examines how behavioral drivers influence capital allocation to ESG assets. It synthesizes emerging trends and new developments by linking investor preferences, beliefs, and trust in disclosure with portfolio rules and market transmission mechanisms. Methods: A structured bibliometric review of Scopus records (2010–2025) was conducted. Performance indicators (yearly publications, citations), source and institutional profiles, and science-mapping techniques were used, including co-authorship density, bibliographic coupling, and keyword co-occurrence. The analysis followed established reporting, and results were summarized through ranked tables and network visualizations. Results: As per the findings, the field expanded strongly after 2019 and peaked in 2024. Finance and operations journals developed portfolio and optimization methods, while sustainability and strategy outlets assessed disclosure credibility, climate salience, and governance practices. Four high-frequency themes had emerged: portfolio construction and risk methods; sustainability policy and disclosure; markets and fund flows; and corporate responsibility and impact. These themes clarified how ESG preferences and perceived credibility were operationalized through screening and tilting and were transmitted to prices and liquidity via flows. Conclusion: The study concludes that ESG allocation is fundamentally shaped by investor preferences and beliefs, operationalized through portfolio design, and transmitted to markets via fund flows. Strengthening disclosure credibility, aligning sustainability screens with risk protocols, and linking stewardship to measurable outcomes emerge as key levers for enhancing trust, performance discipline, and impact. While bibliometric analysis is constrained by database coverage and citation windows, future research should integrate behavioral metrics with portfolio and market microstructure tests to clarify flow-to-price channels and enhance evidence on credibility, salience, and impact. Novelty: The study offers an integrated framework that connects behavioral mechanisms with portfolio implementation and market transmission. It consolidates fragmented evidence into a coherent map of sources, institutions, and themes, and it identifies research priorities that combine behavioral measurement with credible flow-to-price identification.